Lipid-based Transfection Reagents Exhibit Cryo-induced Increase in Transfection Efficiency - Helena Sork; Joel Z Nordin; Janne J Turunen; Oscar PB Wiklander; Burcu Bestas; Eman M Zaghloul; Helerin Margus; Kärt Padari; Adil D Duru; Giulia Corso; Jeremy Bost; Pieter Vader; et al. (Elsevier, 2016)
The advantages of lipid-based transfection reagents have permitted their widespread use in molecular biology and gene therapy. This study outlines the effect of cryo-manipulation of a cationic lipid-based formulation, Lipofectamine 2000, which, after being frozen and thawed, showed orders of magnitude higher plasmid delivery efficiency throughout eight different cell lines, without compromising cell viability. Increased transfection efficiency with the freeze-thawed reagent was also seen with 2'-O-methyl phosphorothioate oligonucleotide delivery and in a splice-correction assay. Most importantly, a log-scale improvement in gene delivery using the freeze-thawed reagent was seen in vivo. Using three different methods, we detected considerable differences in the polydispersity of the different nucleic acid complexes as well as observed a clear difference in their surface spreading and sedimentation, with the freeze-thawed ones displaying substantially higher rate of dispersion and deposition on the glass surface. This hitherto overlooked elevated potency of the freeze-thawed reagent facilitates the targeting of hard-to-transfect cells, accomplishes higher transfection rates, and decreases the overall amount of reagent needed for delivery. Additionally, as we also saw a slight increase in plasmid delivery using other freeze-thawed transfection reagents, we postulate that freeze-thawing might prove to be useful for an even wider variety of transfection reagents.